Weird dinosaurs - Pickrell, John (Columbia University Press, 2016)
"From the outback of Australia to the Gobi Desert of Mongolia and the savanna of Madagascar, the award-winning science writer and dinosaur enthusiast John Pickrell embarks on a world tour of new finds, meeting the fossil hunters who work at the frontier of discovery. He reveals the dwarf dinosaurs unearthed by an eccentric Transylvanian baron; an aquatic, crocodile-snouted carnivore bigger than T. rex that once lurked in North African waterways; a Chinese dinosaur with wings like a bat; and a Patagonian sauropod so enormous it weighed more than two commercial jet airliners. Other surprising discoveries hail from Alaska, Siberia, Canada, Burma, and South Africa. Why did dinosaurs grow so huge? How did they spread across the world? Did they all have feathers? What do sauropods have in common with 1950s vacuum cleaners? The stuff of adventure movies and scientific revolutions, Weird Dinosaurs examines the latest breakthroughs and new technologies that are radically transforming our understanding of the distant past. Pickrell opens a vivid portal to a brand-new age of fossil discovery, in which fossil hunters are routinely redefining what we know and how we think about prehistory's most iconic and fascinating creatures."--Jacket.